ANALISIS NETWORK SLICING DALAM MENINGKATKAN FLEKSIBILITAS LAYANAN PADA JARINGAN 5G: STUDI TINJAUAN LITERATUR SISTEMATIS - Dian Indah Lestari; Vera Veronica; Andi Ahmad Dahlan; Yulindon Khaidir (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
The development of 5G networks requires flexible mechanisms to support increasingly diverse and complex service demands. Network slicing enables the partitioning of a physical network into multiple virtual networks tailored to specific service requirements. This study aims to analyze the role of network slicing in enhancing service flexibility in 5G using a Systematic Literature Review (SLR) approach, focusing on publications from 2020 to 2025. The analysis examines key aspects, including network architecture, enabling technologies such as Software-Defined Networking (SDN), Network Function Virtualization (NFV), and Multi-access Edge Computing (MEC), as well as their application in supporting various 5G service categories. The results indicate that network slicing enables dynamic and efficient resource allocation across heterogeneous services, improves service isolation, and enhances overall network management. It effectively supports major 5G service types, including enhanced Mobile Broadband (eMBB), Ultra-Reliable Low Latency Communications (URLLC), and massive Machine Type Communications (mMTC). However, several challenges remain, such as end-to-end orchestration complexity, interoperability issues, and limited real-world implementation. This study provides a comprehensive overview of network slicing and identifies key research gaps and future research directions.